Jokastina fatalistična etika - Senegačnik, Brane (Keria (Ljubljana), 2002)
While the role of Jocasta in Oedipus Tyrannus is a minor one in itself, her passive attitude and fatalistic credo, set in striking contrast to Oedipus' firm determination to act and thus bring relief to the plague-stricken Thebes, express one of the most important ideas of the play. There are some striking similarities between her words and the ethical principles of the most prominent Hellenistic philosophies, i. e. Stoicism and Epicureanism, as well as those of Martin Heidegger's and his followers' thought. Like these philosophies, Jocasta's words unwittingly reveal an inability to face the tragic reality of human life.
Keywords: epikurejstvo; etika; fatalizem; grška dramatika; grška filozofija; grška tragedija; Jokasta; Sophocles; stoicizem